Formulation and Evaluation of Antimicrobial Herbal Ointment - Chhetri, Himal Paudel; Yogol, Nisha Shrestha; Sherchan, Jyoti; KC, Anupa; Mansoor, S; Thapa, Panna (Kathmandu University Journal of Science Engineering and Technology, 2010)
Most of the antibiotics were originally derived from micro-organisms while the chemotherapeutic agents are from plants. Herbal medicine refers to the use of any plant’s seeds, berries, roots, leaves, bark, or flowers for medicinal purposes. Along with other dosage forms, herbal drugs are also formulated in the form of ointment. An ointment is a viscous semisolid preparation used topically on a variety of body surfaces. The objective of the study was to formulate and evaluate the antimicrobial herbal ointment from the local medicinal plants. The ethanolic extracts of the selected plants were taken in different ratio randomly and the antimicrobial tests of the combinations were carried out. The most effective combination was then determined by comparing the results of the zone of inhibition given by the 10 different extract ratios on Staphylococcus aureus, Escherichia coli and Klebsiella species. Then the minimum inhibitory concentration of the effective combination was found out. The ointment base was prepared and formulation of ointment was done by incorporating the active ingredients in most effective ratio in the base by trituration. After the completion of the formulation, quality of the ointment was assessed in terms of irritancy, spreadability, diffusion and stability.